2020
DOI: 10.21203/rs.3.rs-23642/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolomics Reveals Ecological Significance of Secondary Metabolites in Scutellaria baicalensis under drought stress

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…from the family Rutaceae rapidly biosynthesized two flavone compounds such as isovitexin and vitexin in response to drought stress ( Hu et al., 2021 ). In Scutellaria baicalensis roots, chrysin was accumulated in response to drought stress, and a high concentration of chrysin helps plants to eliminate the excessive ROS produced during drought stress and maintains the equilibrium in plant cells ( Meng et al., 2020 ). Our results showed that cynaroside, eriocitrin, 2′-hydroxygenistein, 2′-hydroxydaidzein, chrysin, neohesperidin, kaempferol 3-neohesperidoside, baimaside, hyperoside, quercitrin, and vitexin were uniquely higher in the leaves of sour orange after drought stress, whereas these compounds were significantly lower or had no obvious difference in pummelo and lemon under drought stress ( Figure 2 ; Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…from the family Rutaceae rapidly biosynthesized two flavone compounds such as isovitexin and vitexin in response to drought stress ( Hu et al., 2021 ). In Scutellaria baicalensis roots, chrysin was accumulated in response to drought stress, and a high concentration of chrysin helps plants to eliminate the excessive ROS produced during drought stress and maintains the equilibrium in plant cells ( Meng et al., 2020 ). Our results showed that cynaroside, eriocitrin, 2′-hydroxygenistein, 2′-hydroxydaidzein, chrysin, neohesperidin, kaempferol 3-neohesperidoside, baimaside, hyperoside, quercitrin, and vitexin were uniquely higher in the leaves of sour orange after drought stress, whereas these compounds were significantly lower or had no obvious difference in pummelo and lemon under drought stress ( Figure 2 ; Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that SOD was strongly expressed in the heart of white-leg shrimp (Penaeus vannamei), stimulated by ROS after one week of culture [58]. S. baicalensis decreased the ROS level and maintained the equilibrium of ROS through biosynthesis [59]. S. baicalensis Georgi flower extract (SFE) could significantly reduce oxidative damage of aging rats by increasing their SOD level in the serum [60].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that SOD was strongly expressed in the heart of white-leg shrimp (Penaeus vannamei), stimulated by ROS after one week of culture [58]. S. baicalensis decreased the ROS level and maintained the equilibrium of ROS through biosynthesis [59]. S. baicalensis Georgi flower extract (SFE) could significantly reduce oxidative damage of aging rats by increasing their SOD level in the serum [60].…”
Section: Phosphatase Can Catalyze the Hydrolysis Of Various Phosphoro...mentioning
confidence: 99%